Pengaruh Komunikasi Pemasaran Digital dan Electronic Word Of Mouth (E-Wom) Terhadap Keputusan Berkunjung pada Ekowisata Mangrove Wonorejo Surabaya - Andry Herawati; Fandy Syahputra; Damajanti Sri Lestari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study investigates how digital marketing communication and electronic word of mouth (e-WOM) shape tourists’ decisions to visit Wonorejo Mangrove Ecotourism in Surabaya. The research was conducted using a quantitative design with a causal–associative framework, involving 96 respondents selected through purposive sampling. Data were gathered using a structured Likert-scale questionnaire and processed using multiple linear regression analysis. The findings demonstrate that digital marketing communication and e-WOM collectively exert a statistically significant and positive influence on tourists’ visiting decisions. In addition, each variable independently contributes a significant positive effect to the decision-making process. The determination coefficient reveals that a substantial portion of variance in visiting decisions is accounted for by the combined role of digital marketing communication and e-WOM. These results underline the critical role of strengthening digital communication strategies and systematically managing online consumer-generated content to improve destination attractiveness and encourage tourist visitation in ecotourism contexts.